MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR KALOR MELALUI MODEL MAKE A MATCH SMPN 11 PONTIANAK - Suwanda, Florensius; Tandililing, Edy; B. Arsyid, Syaiful (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research purpose to improve student learning activities and outcomes through learning models make a match on the heat leasson. This rearch method applied Arikunto cycle classroom action research (CAR). The subjects of this research is class VIID public junior high school 11 of Pontianak. Data collection includes (1) observation sheets to observe learning activities, (2) Preliminary test and final test. Student learning activities that are intended to ask, answer, refute and cooperative while the teacher activity application of the make a match learning model. Data obtained indicated an increase student learning activities that are in the category of very active and active ftrom cycle I to cycle II of 1,58% from 76.47% to 90,05%. The results of data analysis show learning outcomesof student who reach the KKM has incteast. The increase learning outcomes in the first cycle was 64,8% while the increase in learning outcomes in the second cycle was 61,8% The results of this study indicate make a match learning model can increase activity and the results increase so other rearcheers can also apply this learning model with motes on studying and understanding the rules of CAR and the steps of learning to make a match.Keywords: Classroom Action Research, Head, Learning Activities, Learning Outcomes, Make a Match, Â